Prevalence, Host Range, and Comparative Genomic Analysis of Temperate Ochrobactrum Phages - Jäckel, Claudia; Hertwig, Stefan; Scholz, Holger C.; Nöckler, Karsten; Reetz, Jochen; Hammerl, Jens A. (Frontiers in Microbiology, 2017)
Ochrobactrum and Brucella are closely related bacteria that populate different habitats and differ in their pathogenic properties. Only little is known about mobile genetic elements in these genera which might be important for survival and virulence. Previous studies on Brucella lysogeny indicated that active phages are rare in this genus. To gain insight into the presence and nature of prophages in Ochrobactrum, temperate phages were isolated from various species and characterized in detail. In silico analyses disclosed numerous prophages in published Ochrobactrum genomes. Induction experiments showed that Ochrobactrum prophages can be induced by various stress factors and that some strains released phage particles even under non-induced conditions. Sixty percent of lysates prepared from 125 strains revealed lytic activity. The host range and DNA similarities of 19 phages belonging to the families Myoviridae, Siphoviridae or Podoviridae were determined suggesting that they are highly diverse. Some phages showed relationship to the temperate B. inopinata phage BiPB01. The genomic sequences of the myovirus POA1180 (41,655 bp) and podovirus POI1126 (60,065 bp) were analysed. Phage POA1180 is very similar to a prophage recently identified in a Brucella strain isolated from an exotic frog. The POA1180 genome contains genes which may confer resistance to chromate and the ability to take up sulfate. Phage POI1126 is related to podoviruses of Sinorhizobium meliloti (PCB5), Erwinia pyrifoliae (Pep14) and Burkholderia cenocepacia (BcepIL02) and almost identical to an unnamed plasmid of the O. intermedium strain LMG 3301. Further experiments revealed that the POI1126 prophage indeed replicates as an extrachromosomal element. The data demonstrate for the first time that active prophages are common in Ochrobactrum and suggest that atypical brucellae also may be a reservoir for temperate phages.